Diplomacy and Narrative Negotiation in China-Kazakhstan Documentaries - Peng, Wang; Myssayeva, K.; Akynbayeva, A. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2026)
The primary objective of the study is to focus on the documentary films “Hello, Kazakhstan” and “Win-Win” as core cases. The research reveals that these documentaries achieve a symbiotic construction of the national image and transmission of political consensus through three interconnected mechanisms: negotiated perspective selection, nested discourse distribution, and intertextual symbol construction. The significance of this work breaks through the limitations of the traditional "center-periphery" binary framework and constructs a three-dimensional analytical model for power negotiation in the context of multi- agent co-narration. This deepens the elaboration of narrative power theory’s micro- mechanisms in cross-cultural cooperation contexts. The study employs qualitative methods, using these two documentaries as case studies to analyze the China-Central Asia media diplomacy practice. Key findings reveal that, practically, the findings offer transferable strategies for China-Central Asia media diplomacy: (1) Cultural cooperation; (2) Economic narratives; (3) Regional communication to strengthen the foundation of cultural identity. Conclusions drawn from these insights provide a concrete paradigm for balancing national subjectivity and regional cohesion in non- Western cross-cultural communication. The results are valuable for media practices, guiding journalists and media organizations toward responsible coverage of media diplomacy practice patterns from a regional and country-specific perspective, but also offer theoretical reference for understanding innovative paths of cross- cultural narrative in non-Western contexts.